Assistance of Publishing Article on Open Journal System for English Teachers Association Members (MGMP) in South Kalimantan - Noor Aida Aflahah; Dina Rafidiyah; Ahmad Kailani; Rezqan Noor Farid (OMNICODE Journal (Omnicompetence Community Developement Journal), 2022)
The publication of articles is a place for teachers to share their teaching experiences. In addition, the publication of articles can support the careers of teachers in promotion. However, it was found that teachers had difficulty in publishing their writings in the Open Journal System. This community service activity aims to provide assistance to English teachers’ association members (MGMP) in South Kalimantan region. Six groups of teachers joined the assistance project, but only two groups can finally submit their papers in the online journal system. The method used is lecture, simulation and discussion through Zoom Meeting. The results of the community service showed that teachers can publish their scientific papers on the Open Journal System. The teachers’ problem is they confuse how to finish writing their scientific papers before they can submit it. While the submission is not really difficult for them, but of course they need some guidance and practice to do it correctly